KEPATUHAN KONSUMSI TABLET FE IBU HAMIL DI WILAYAH KERJA PUSKESMAS LUBUK BEGALUNG - Eka Trio Effandilus; Sri Mindayani; Fadhila Tunnisa (Bajang Institute, 2025)
Compliance with Fe tablet consumption is important for pregnant women to prevent health problems during pregnancy. Low consumption of Fe tablets in pregnant women has a very large impact such as high rates of anemia, high rates of fetal morbidity and mortality, abortion and the main cause of maternal death due to bleeding after birth. Data from the Lubuk Begalung Health Center shows that only 74.45% of pregnant women receive Fe tablets. The aim of the study was to determine factors of compliance with Fe tablet consumption in pregnant women in the Lubuk Begalung. Type of quantitative research with a cross sectional design. A sample of 87 people was taken using a multistage random sampling. The analysis using the Chi Square test and multiple logistic regression. The results of showed that 48.3% of mothers were disobedient in consuming Fe tablets, 54% of mothers had poor knowledge, 62.1% of mothers had negative attitudes, and 57.5% of mothers had poor support. The results of bivariate show that is a significant relationship between knowledge (p-value=0.001), attitude (pvalue=0.001), and family/ husband support (p-value= 0.002) with adherence to consuming Fe tablets in pregnant women. The results of the multivariate showed that the most dominant variable related to compliance with the consumption of Fe tablets was knowledge with OR : 7.5. This means that pregnant women who have poor knowledge have a 7.5 times chance of not complying with taking Fe tablets. It is recommended to increase education for pregnant women.